Neonatal morbidity and mortality associated with low adherence to prenatal corticosteroids - Rene O. Pérez-Ramírez; Juan Carlos Lona-Reyes; Cesar A. Ochoa-Meza; Larissa M. Gómez-Ruiz; Ruth Y. Ramos-Gutiérrez; E. Elizabeth Camarena-Pulido; J. Antonio Gallegos-Marín (Elsevier, 2019)
Introduction: Prenatal corticosteroids reduce neonatal mortality and morbidity; however, there are few studies in developing countries, and with inconsistent results. The purpose of this study was to quantify the frequency of the use of prenatal corticosteroids and to estimate its effect on the morbidity and mortality of premature newborns. Methods: A retrospective cohort study was performed on premature newborns selected from a census conducted between January 2016 and August 2017. The use of corticosteroids was taken from the maternal records, and the dependent variables from the neonatal records. An analysis was made of the relationship using logistic regression, adjusted to gestational age and weight. Results: The study included 1083 premature infants of which 53.3% were male. The mean gestational age was 33.4 weeks. Corticosteroids were received by 42%, with latency ≥24 h in 23.6% and ≥48 h in 13.8%. Respiratory distress syndrome was observed in 35% (379/1083), early neonatal sepsis in 4.4% (48/1083), late neonatal sepsis in 10.7% (116/1083), intraventricular haemorrhage in 15.1% (137/908), chronic lung disease in 51.4% (165/321), and death in 22.3% (242/1083). Prenatal corticosteroids decreased the risk of death in children under 34 weeks (OR 0.63, 95% CI 0.40-0.98). The decrease was greater if they presented with latency ≥48 h (OR 0.40, 95% CI 0.20-0.80). The rest of the dependent variables were not modified by the intervention. Conclusions: In preterm infants, 42% received antenatal corticosteroids. In those with less than 34 weeks, there was a decrease in the risk of death without changes in morbidity. Resumen: Introducción: Los corticosteroides prenatales disminuyen la morbimortalidad neonatal, sin embargo, existen pocos estudios en países en vías de desarrollo, con resultados no consistentes. El objetivo fue cuantificar la frecuencia del uso de corticosteroides prenatales y estimar su efecto en la morbimortalidad de recién nacidos prematuros. Métodos: Estudio de cohorte retrospectivo; se seleccionaron los recién nacidos prematuros de un censo realizado entre enero de 2016 y agosto de 2017. De los expedientes maternos se registró el uso de corticosteroides; y de los expedientes de los neonatos se indagó las variables dependientes. La asociación se analizó con regresión logística, ajustada a la edad gestacional y el peso. Resultados: Se estudiaron 1.083 prematuros, el 53,3% de género masculino; la edad gestacional promedio fue 33,4 semanas. Recibieron corticosteroides el 42%, con latencia ≥24 horas el 23,6% y ≥48 horas el 13,8%. Presentaron síndrome de dificultad respiratoria el 35% (379/1083), sepsis neonatal temprana el 4,4% (48/1083), sepsis neonatal tardía el 10,7% (116/1083), hemorragia intraventricular el 15,1% (137/908), enfermedad pulmonar crónica el 51,4% (165/321) y muerte el 22,3% (242/1083). Los corticosteroides prenatales disminuyeron el riesgo de muerte en menores de 34 semanas (OR: 0,63, IC 95%: 0,40-0,98); el decremento fue mayor si presentaron latencia ≥48 horas (OR: 0,40; IC 95%: 0,20-0,80). El resto de variables dependientes no se modificó por la intervención. Conclusiones: El 42% de los prematuros recibe corticosteroides prenatales. En menores de 34 semanas se observó una disminución del riesgo de muerte sin modificación en la morbilidad.